HOW SCHOOL FACILITIES AND PEER RELATIONSHIPS AFFECT STUDENT’S CONCENTRATION - Ikhwandaru, Ezra; Kartikowati, Rr Sri; Fidyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This research aimed to investigate the impact of school facilities and peer groups on students' concentration in learning partially at SMKN 62 Jakarta. The study used a quantitative approach. The population comprised all 532 students at the school. By applying the Slovin formula with a 5% margin of error, a proportionate random sampling method was used to select 228 students as the sample. Data analysis was carried out using the SEM PLS technique with the assistance of SmartPLS 4.0 software. The analysis process involved assessing the measurement model, structural model, and testing hypotheses related to direct effects. The results of this study are that there is an influence between school facilities on students' learning concentration, and there is an influence between peer groups on students' learning concentration at SMKN 62 Jakarta.